Functional tooth units and masticatory ability in elderly population - Dwiningrum, Fatimah Rini; Sari, Kartika Indah; Rikmasari, Rasmi (Padjadjaran Journal of Dentistry, 2021)
Introduction: The elders are the ones that most often experience tooth loss which affects masticatory function. Masticatory function can be evaluated subjectively through masticatory ability assessment. The masticatory function is influenced by the number of posterior occluding pairs; this also may be called as functional tooth units (FTUs). The purpose of this study was to describe FTUs and masticatory ability in the elderly. Methods: This research was a descriptive study with a cross-sectional study design. Subjects were taken by purposive sampling technique. The study was conducted in the Lebakgede Sub-district, Bandung City. Data mentioned were obtained by conducting interviews regarding data on subject characteristics and questionnaires of masticatory ability, as well as examining the oral cavity to obtain FTUs data. Results: Subjects obtained were 74 people consisting of 63 women (85.14%) and 11 men (14.86%). Based on the results, the average age of the research subjects was 68.49 years, and those with good masticatory ability status were 26 elderly (35.14%) with an average FTU value of 5.9 while 48 elderly (64.86%) had poor masticatory ability status with an average FTU score of 1.5, even 31 subjects (41.89%) had a zero FTU score. Conclusion: The majority of the elderly in this research mostly had a low total FTUs score which means that the masticatory ability status in the elderly tended to be poor.